2019
DOI: 10.1159/000503707
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement by an Expert Panel on the Diagnosis and Management of Iron Deficiency Anemia in the Gulf Cooperation Council Countries

Abstract: Background: Iron deficiency (ID) and ID anemia (IDA) are common in the member states of the Gulf Cooperation Council (GCC). The unique genetic and lifestyle factors of the patient population in the region have necessitated the development of recommendations to help educate health-care professionals on appropriate diagnosis and management of ID/IDA. Methods: A panel of regional experts, including gastroenterologists and hematologists with expertise in the treatment of IDA, was convened to develop regional pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Hemoglobin is often low in these patients and confounds diagnosis between IDA and/or thalassemia. In such cases, serum ferritin should be measured to assess body iron stores and hemoglobin electrophoresis should be used to rule out thalassemia 49 . Specialized tests such as serum soluble transferrin receptor (sTfR) concentrations and the ferritin index (sTfR level/log ferritin) can be used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoglobin is often low in these patients and confounds diagnosis between IDA and/or thalassemia. In such cases, serum ferritin should be measured to assess body iron stores and hemoglobin electrophoresis should be used to rule out thalassemia 49 . Specialized tests such as serum soluble transferrin receptor (sTfR) concentrations and the ferritin index (sTfR level/log ferritin) can be used.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, serum ferritin should be measured to assess body iron stores and hemoglobin electrophoresis should be used to rule out thalassemia. 49…”
Section: General Considerations In Diagnosismentioning
confidence: 99%
“…Anemia is a health burden in the Gulf countries, with the prevalence of IDA ranging from 25% to 35%, and 12.9% of males aged 11–19 years contributing to it [ 17 , 18 ]. In our previous study on anemia among Jazan university students, we found 4.7% of males had anemia, but the finding might be biased due to sampling in a specific population and low sample size [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of chronic anaemia and diffuse IO might dramatically impact pregnancy outcome [ 157 , 158 ]. Anaemia represents a complication of minor BTH, but also iron-deficient anaemia is expected during physiological pregnancies [ 158 ].…”
Section: Pregnancy Outcomementioning
confidence: 99%